(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
After WWII in Serbia/former Yugoslavia new possibilities opened up for women – they gained voting rights, considerable collective and reproductive rights and institutional support for doing jobs which had been exclusively male up to that point. Even though it was delayed, the feminization of certain professions continued to evolve. The state supported and emphasized the development of science during this period, which enabled a number of women to be the in the frontline of the development of natural sciences. As early as 1946 Dragica Nikolić and Branka Radivojević became the first women who worked as assistant professors of physics at the University of Belgrade. At the Institute for Nuclear Sciences Vinča (founded in 1948) and the Institute for Physics (founded in 1961), women have been present from the very beginning. Some of them, such as Mira Jurić or Branislava Nešković Perović, who was the only woman director of the Vinča Institute (1976-1979), greatly contributed to the development of nuclear physics even at the international level. There are many interesting stories of the women scientists who lived and worked with their professional and personal partners in the modest premises of the Institute. Still, to what extent were they visible outside their laboratories? What do we know about them today? What kind of trace did they leave professionally and publicly? Were they and do they remain invisible?